Toward an Ecology of Career Development - Young, Richard A. (Canadian Journal of Counselling and Psychotherapy, 2011)
In this article, a case is made for the application of the ecological metaphor to career development. The argument is framed in response to two diverse trends having evolved in career development theory and research, one psychological and the other sociological. The ecological approach is described, and several applications to career development are made. Ecology is found to focus specifically on the interaction between the developing person and the environment. It also represents a special application of general systems theory. Contrasts between an ecological perspective and more traditional approaches to career development are provided. In the final section of the paper the implications of this perspective for research and practice are discussed.